Flashing Lights, Dark Shadows, and Future Prospects of the Current European Legislation for a Better Traceability and Animal Health Requirements for Movements of Small Animal Germinal Products - Pugliese, Michela; Monti, Salvatore; Biondi, Vito; Marino, Gabriele; Passantino, Annamaria (Frontiers in Veterinary Science, 2022)
Recently, there has been an increasing movement of germinal products of dogs (Canis lupus familiaris) and cats (Felis silvestris catus) between the Member States. Therefore, Europe laid down and harmonized rules on the marking of straws and other packages containing germinal products (Commission Delegated Regulation (EU) 2020/686). Given that germinal products’ movement may increase the risk of infectious disease spread, requirements regarding animal health have been revised focusing on control of rabies and echinococcosis, although there are new emerging diseases that may require, even locally, specific requirements. For this reason, veterinarians, operators, and official veterinarians are involved in different phases of the process. Because non-veterinary operators can operate in all phases, they should have a limited role in collecting germinal products, especially for feline species. Veterinarians, instead, should have a main role in the health evaluation of donors, in collecting germ cells with medical techniques and in depositing sperm and embryos with endoscopic or surgical methods. The official veterinarians are the main ones responsible for the application of the rules. This paper aims to provide an overview of the European legislative framework regarding the newly delegated regulation on germinal products in small animals (dogs and cats), highlighting some of the benefits and critical aspects regarding its functioning.